Effect of near-field earthquake on isolated bridge considering soil–structure interaction. Issue 4 (9th September 2019) - Naghibi, Amireddin; Javadi, Pasha; Zarfam, Panam
Abstract : In the 1995 Kobe earthquake, different bearing fractures were observed in isolated bridges. Piers and bearings were the first and second vulnerable structural elements. The estimation load due to far-field earthquakes can be calculated using BS EN 1998-1:2004, but research on this issue for near-field earthquakes is limited. The aim of this study was to verify the effect of the vertical component of near-field earthquakes on structural responses and compare the results with values suggested using BS EN 1998-1:2004. An isolated bridge was designed based on Eurocode standards and modelled in OpenSees. Moreover, since soil–structure interaction (SSI) has an inherent effect on bridge structures, the induced vertical accelerations were compared with and without SSI effects. It was found that vertical acceleration decreased in the model including SSI effects. The shear strain of the elastomers was found to be within the range allowed by BS EN 1998-2:2005.